Herpes Simplex Virus DNA Cleavage and Packaging: Association of Multiple Forms of U(L)15-Encoded Proteins with B Capsids Requires at Least the U(L)6, U(L)17, and U(L)28 Genes - Salmon, Brandy (American Society for Microbiology, 1998)
The U(L)15 gene of herpes simplex virus (HSV) is one of several genes required for the packaging of viral DNA into intranuclear B capsids to produce C capsids that become enveloped at the inner nuclear membrane. A rabbit antiserum directed against U(L)15-encoded protein recognized three proteins with apparent M(r)s of 79,000, 80,000, and 83,000 in highly purified B capsids. The 83,000-M(r) protein was detected in type C capsids and comigrated with the product of a U(L)15 cDNA transcribed and translated in vitro. The 83,000- and 80,000-M(r) proteins were readily detected in purified virions. Inasmuch as (i) none of these proteins were detectable in capsids purified from cells infected with HSV-1(ΔU(L)15), a virus lacking an intact U(L)15 gene, and (ii) corresponding proteins in capsids purified from cells infected with a recombinant virus [HSV-1(R7244), containing a 20-codon tag at the 3′ end of U(L)15] were decreased in electrophoretic mobility relative to the wild-type proteins, we conclude that the proteins with apparent M(r)s of 83,000, 80,000, and 79,000 are products of U(L)15 with identical C termini. The 79,000-, 80,000-, and 83,000-M(r) proteins remained associated with B capsids in the presence of 0.5 M guanidine HCl and remained detectable in capsids treated with 2.0 M guanidine HCl and lacking proteins associated with the capsid core. These data, therefore, indicate that U(L)15-encoded proteins are integral components of B capsids. Only the 83,000-M(r) protein was detected in B capsids purified from cells infected with viruses lacking the U(L)6, U(L)17, or U(L)28 genes, which are required for DNA cleavage and packaging, suggesting that capsid association of the 80,000- and 79,000-M(r) proteins requires intact cleavage and packaging machinery. These data, therefore, indicate that capsid association of the 80,000- and 79,000-M(r) U(L)15-encoded proteins reflects a previously unrecognized step in the DNA cleavage and packaging reaction.